2023
DOI: 10.3390/ijms24032411
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-Dependent Effects of the Selenium-Sorafenib Nanocomplex on Glioblastoma Cells and Astrocytes of the Cerebral Cortex: Anticancer Agent and Cytoprotector

Abstract: Despite the fact that sorafenib is recommended for the treatment of oncological diseases of the liver, kidneys, and thyroid gland, and recently it has been used for combination therapy of brain cancer of various genesis, there are still significant problems for its widespread and effective use. Among these problems, the presence of the blood–brain barrier of the brain and the need to use high doses of sorafenib, the existence of mechanisms for the redistribution of sorafenib and its release in the brain tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 68 publications
1
10
0
Order By: Relevance
“…For example, SeNPs initiated the chemosensitivity of fluorouracil nanoparticles in the breast and colon cancer cell lines [ 152 ]. Another study documented that the Se–sorafenib nanocomplex could bypass the chemoresistance in glioblastoma cells [ 153 ]. It is of particular interest that this Se–sorafenib nanocomplex induced the apoptosis of cancer cells via Ca 2+ -dependent endoplasmic reticulum stress.…”
Section: Seleniummentioning
confidence: 99%
“…For example, SeNPs initiated the chemosensitivity of fluorouracil nanoparticles in the breast and colon cancer cell lines [ 152 ]. Another study documented that the Se–sorafenib nanocomplex could bypass the chemoresistance in glioblastoma cells [ 153 ]. It is of particular interest that this Se–sorafenib nanocomplex induced the apoptosis of cancer cells via Ca 2+ -dependent endoplasmic reticulum stress.…”
Section: Seleniummentioning
confidence: 99%
“…On the other hand, as indicated above, nanoselenium affects the expression of ER-resident selenoproteins involved in the regulation of intracellular Ca 2+ ion concentration. It was found that the incubation of cortical astrocytes with SeNPs for 24 h leads to the depletion of the Ca 2+ pool of the ER, and this depletion of the Ca 2+ pool is correlated with the activation of proteins responsible for the activation of adaptive ER stress [ 172 ]. However, these mechanisms require detailed study.…”
Section: Selenium Nanoparticles In Protecting Cells From Ischemic Fac...mentioning
confidence: 99%
“…Hyaluronic acid (A549 cells), ATP (depletion of mitochondrial membrane potential and oxidative stress) and other agents were also described [69,70]. The addition of anticancer agents (sorafenib) to SeNPs significantly increases the activity of others against aggressive cancer lines (increased calcium entry, ER stress and apoptosis of HepG2, gliablastoma A-172) [49,71,72]. Oridoni/SeNP composites have anticancer activity and reduce the viability of RAW264.7, KYSE-150 and EC970 cancer cells by ~50% [73].…”
Section: Number Of Publications Per Yearmentioning
confidence: 99%